2013
DOI: 10.1021/jo402118j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of QS-21-Based Immunoadjuvants

Abstract: Three structurally defined QS-21-based immune adjuvant candidates (2a-2c) have been synthesized. Application of the two-stage activation glycosylation approach utilizing allyl glycoside building blocks improved the synthetic accessibility of the new adjuvants. The efficient synthesis and establishment of the stand-alone adjuvanticity of the examined synthetic adjuvant (2b) open the door to the pursuit of a new series of structurally defined QS-saponin based synthetic adjuvants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 39 publications
0
42
1
Order By: Relevance
“…Whereas hydrolysis of the acyl chain resulted in deacylated saponins that did not stimulate T H 1 immunity or cytotoxic T lymphocyte induction but, rather, T H 2 immunity (significant IgG1 antibody levels but poor IgG2a/IgG2b responses) 25 , replacing the original acyl chain by the dodecylamide at the branched trisaccharide in GPI-0100 restored T H 1 immunity and the ability to induce cytotoxic T lymphocyte responses 26 . Chemical synthesis of the presumably main immunoactive constituents of GPI-0100, based on QS-21 and QS-17/18, confirmed the adjuvant activity of the heterogeneous GPI-0100 adjuvant, albeit at doses five times higher than QS-21 itself 27 , 28 . To study further the acylation effect in saponin adjuvant activity, Wang et al synthesized and immunologically evaluated two C28 pentasaccharide analogues of QS-7 with a single-sugar truncation and showed that acetylation at the 3-O and 4-O positions of the fucosyl unit (Fig.…”
Section: Saponin-based Adjuvantsmentioning
confidence: 80%
“…Whereas hydrolysis of the acyl chain resulted in deacylated saponins that did not stimulate T H 1 immunity or cytotoxic T lymphocyte induction but, rather, T H 2 immunity (significant IgG1 antibody levels but poor IgG2a/IgG2b responses) 25 , replacing the original acyl chain by the dodecylamide at the branched trisaccharide in GPI-0100 restored T H 1 immunity and the ability to induce cytotoxic T lymphocyte responses 26 . Chemical synthesis of the presumably main immunoactive constituents of GPI-0100, based on QS-21 and QS-17/18, confirmed the adjuvant activity of the heterogeneous GPI-0100 adjuvant, albeit at doses five times higher than QS-21 itself 27 , 28 . To study further the acylation effect in saponin adjuvant activity, Wang et al synthesized and immunologically evaluated two C28 pentasaccharide analogues of QS-7 with a single-sugar truncation and showed that acetylation at the 3-O and 4-O positions of the fucosyl unit (Fig.…”
Section: Saponin-based Adjuvantsmentioning
confidence: 80%
“…The QA-trisaccharide conjugate 6 (30 mg, 0.01 mmol) 21 and the side chain 7 (11 mg, 0.03 mmol) in 1.0 mL of chloroform were treated with HATU (14 mg, 0.04 mmol) and N,N -diisopropylethylamine (11 μ L, 0.06 mmol) at room temperature overnight. The reaction mixture was then concentrated and purified directly with column chromatography on silica gel (eluted with PE/EtOAc gradient) to afford the amide 20x (31 mg, 94%) as a white amorphous solid: R f = 0.6 (PE/EtOAc, 1:1); [ α ] D 23 = −28.8 ( c = 1.53, CHCl 3 ); 1 H NMR (400 MHz, CDCl 3 ) (characteristic protons) δ 9.68 (s, 1 H), 7.37−7.33 (m, 5 H), 6.11 (t, J = 5.5 Hz, 1 H), 5.44 (d, J = 7.8 Hz, 1 H), 5.28 (m, 1 H), 5.20 (d, J = 3.2 Hz, 1 H), 5.10−4.82 (m, 10 H), 4.79 (dd, J = 7.8, 5.8 Hz, 1 H), 4.58 (d, J = 6.0 Hz, 1 H), 4.55 (d, J = 7.3 Hz, 1 H), 4.52 (d, J = 7.0 Hz, 1 H), 4.48 (s, 1 H), 4.41 (d, J = 7.3 Hz, 1 h), 4.26 (d, J = 7.2 Hz, 1 H), 4.10 (dd, J = 12.0, 4.6 Hz, 1 H), 4.05 (dd, J = 11.9, 4.9 Hz, 1 H), 3.94 (s, 1 H), 3.90 (t, J = 8.1, 1 h), 3.84−3.65 (m, 7 H), 3.65−3.53 (m, 4 H), 3.50 (m, 1 H), 3.40−3.15 (m, 7 H), 3.12 (t, J = 10.0 Hz, 1 H), 2.83 (d, J =11.6 Hz, 1 H), 2.35 (t, J = 7.6 Hz, 2 h), 2.25−2.20 (m, 1 H), 2.15 (s, 3 H), 2.10 (s, 3 H), 2.09−2.00 (m, 20 H), 1.20 (d, J = 6.2 Hz, 3 H), 1.07 (d, J = 6.2 Hz, 3 H), 1.02−0.81 (m, 91 H), 0.79 (s, 3 H), 0.78−0.55 (m, 50 H); 13 C NMR (176 MHz, CDCl 3 ) δ 212.2, 175.6, 173.7, 170.4, 170.2, 170.1, 169.9, 169.7, 169.4, 169.2, 169.1, 168.2, 143.4, 136.1, 128.5, 128.4, 128.3, 128.2, 121.6, 108.3, 107.3, 105.8, 104.7, 102.9, 102.4, 101.4, 101.3, 100.7, 100.6, 98.4, 93.9, 79.6, 78.8, 78.7, 77.5, 76.3, 76.2, 76.1, 75.8, 75.7, 75.4, 75.0, 72.6, 72.47, 72.45, 72.0, 71.6, 71.4, 71.36, 70.3, 70.27, 70.0, 69.8, 69.5, 69.2, 68.7, 68.2, 66.1, 65.4, 62.4, 61.5, 60.4, 57.7, 56.0, 53.9, 49.5, 49.3, 46.8, 46.1, 41.7, 40.9, 39.9, 39.3, 38.1, 36.1, 35.1, 34.5, 34.3, 32.8, 32.5, 31.9, 30.7, 30.5, 29.7, 29.6, 29.4, 29.3, 29.2, 29.1, 27.0, 26.4, 25.8, 24.9, 24.3, 23.4, 22.7, 21.0, 20.9, 20.8, 20.7, 20.6, 20.57, 20.53, 20.3, 17.7, 17.5, 15.92, 15.90, 14.1, 12.1, 7.6, 7.5, 7.3, 7.2, 7.1, 7.05, 6.9, 6.8, 5.9, 5.6, 5.4, 5.3, 5.26, 5.23, 5.22, 5.0, 4.4; IR (neat) 2952, 2875, 1750; MS (MALDI) m/e [M + Na] + (rel intens) calcd for C 159 H 279 NNaO 46 Si 9 3214.7378 (100.0), 3215.7411 (85.4), 3213.7344 (58.1), 3216.7445 (48.4), 3215.7374 (45.7), 3216.7407 (39.0), 3216.7346 (30.1), 3214.7340 (26.6), 3217.7380 (25.7), 3217.7441 (22.1), 3217.7479 (20.4), 3215.7313 (17.5), 3218.7413 (14.6), 3217.7342 (12.2), 3218.7376 (10.5), found 3213.420, 3214.436, 3215.444, 3216.446, 3217.446, 3218.446.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the early work of Marciani et al on GPI-0100 1215,19 and the structure–function studies of Soltysik et al 20 provide us a valuable clue on the initial molecular design of QS analogues (as shown in Figure 1). We have recently synthesized structurally defined 2a and 2x , 21 the QS-21-derived components in GPI-0100. 12,16 The stand-alone adjuvant activity of 2x confirmed that our new design is a feasible path to chemically stable QS-based saponin adjuvants.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobic effect is assumed to be one of the driving forces for passive transport of xenobiotics through bio-membranes and, to a certain degree, responsible for interactions with receptors. This property determining the biological activity of substances was first recognized by Overton, Meyer and Baum [ 2 , 4 ], and since that time hundreds of articles, among them some review papers, on the lipophilic properties of different bioactive compounds in medicine, agriculture or environmental chemistry have appeared [ 9 16 ].…”
Section: Introductionmentioning
confidence: 99%